A recent decision involving the Italian rules of private international law on the protection of adults - Franzina, Pietro (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
A recent decision by the Tribunal of Belluno provides the opportunity to discuss the difficulties that surround the application of the Italian rules of private international law concerning the protection of adults who, by reason of an impairment or insufficiency of their personal faculties, are not in a position to protect their interests. Seised of a request for the appointment of an “amministratore di sostegno” (a person charged with assisting the adult concerned in the taking of particular decisions), the Tribunal found it had jurisdiction on the ground that the person for whom the protection was sought – a national of Macedonia – resided in Italy. As noted by the Tribunal, this provided a sufficient basis for jurisdiction under both Article 3 and Article 9 of the Italian Statute on Private International (Law No 218 of 1995), concerning jurisdiction over contentious and non-contentious proceedings, respectively. As regards the applicable law, the Tribunal observed at the outset that, pursuant to Article 43 of the Italian Statute, the protection of adults is governed by the law of the State of nationality of the adult concerned, that is, in the circumstances, the law of Macedonia. The Tribunal went on to assess whether the conflictof-laws rules in force in Macedonia refer, in turn, to the law of the different country, and found that they refer the matter back to Italian law. Like the Italian Statute, the Macedonian Statute of Private International Law provides that the protection of adults be governed by the law of nationality of the adult in question. However, the Macedo-nian Statute includes a general exception clause pursuant to which, in the Tribunal’s view, the case must rather be considered to be governed by Italian law, given that the case is con-nected with Italy in all respects, apart from the nationality of the person concerned. Hence, according to Article 13 of the Italian Statute, on renvoi, the application of Italian law. The Tribunal’s complex reasoning, while persuasive in itself, illustrates the reasons why the cur-rent legal landscape hardly suits the interests underlying this area of law, in particular as they result from the United Nations Convention on the rights of persons with disabilities of 2006. The paper argues that the picture would significantly improve if Italy ratified the Hague Convention of 2000 on the international protection of adults.
Keywords: disability; capacity; assisted decision-making; jurisdiction; contentious and non-contentious proceedings; applicable law; renvoi; exception clause